Successful treatment of hepatitis C virus infection with sofosbuvir and simeprevir in the early phase of an allogeneic stem cell transplant. Issue 1 (9th February 2016) - Piñana, J.L.; Serra, M.Á.; Hernández‐Boluda, J.C.; Navarro, D.; Calabuig, M.; Solano, C.
Abstract: Currently, a lack of consensus exists on how to manage a hepatitis C virus (HCV) infection after allogeneic hematopoietic stem cell transplantation (allo‐HSCT). Ribavirin alone, or in combination with interferon, has been the mainstream therapy for HCV infection after transplantation. However, very few patients have been regularly treated owing to concerns about poor tolerability, frequent side effects, and limited efficacy. The present case illustrates the striking efficacy of the combination therapy of sofosbuvir with simeprevir, early after transplantation, as it was able to completely eliminate viral replication within 1 month of initiation of treatment. Moreover, tolerance was good, with only minor interactions between the immunosuppressive drugs. This case report supports the feasibility of using this combination therapy early after allo‐HSCT for patients with HCV infection.